2012
DOI: 10.1099/jmm.0.036939-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro time-kill studies of antimicrobial agents against blood isolates of imipenem-resistant Acinetobacter baumannii, including colistin- or tigecycline-resistant isolates

Abstract: The emergence of colistin or tigecycline resistance as well as imipenem resistance in Acinetobacter baumannii poses a great therapeutic challenge. The bactericidal and synergistic effects of several combinations of antimicrobial agents against imipenem-, colistin-or tigecyclineresistant A. baumannii isolates were investigated by in vitro time-kill experiments. Six imipenemresistant A. baumannii blood isolates were examined in this study, including colistin-and tigecycline-susceptible, colistin-resistant but ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 31 publications
(33 reference statements)
1
34
0
1
Order By: Relevance
“…In an in vitro study in 2010, Ozbek and Senturk [31] reported the synergistic effect of Col+Tig against meropenem resistant ABC. In a study in 2012, Peck et al [32] reported that this combination was synergistic and had bactericidal effects even at 0.5x MIC antibiotic concentration. Therefore, we also assume that tigecycline may be another combination alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro study in 2010, Ozbek and Senturk [31] reported the synergistic effect of Col+Tig against meropenem resistant ABC. In a study in 2012, Peck et al [32] reported that this combination was synergistic and had bactericidal effects even at 0.5x MIC antibiotic concentration. Therefore, we also assume that tigecycline may be another combination alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies reported synergistic effects between diverse drugs for the treatment of Acinetobacter [26,[29][30][31][32]37] . However, more in vivo studies about these combinations are needed to provide high grade of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro interaction synergy studies against KPC or carbapenem-resistant Acinetobacter spp. have revealed promising effects of tigecycline in combination [14,15]. Despite the demonstration of an adequate activity against Acinetobacter species of clinical significance [14], the question regarding whether tigecycline constitutes an effective option against resistant Acinetobacter spp.…”
mentioning
confidence: 99%
“…Most synergy studies against A. baumannii, however, are conducted in vitro by applying time-kill or checkerboard methodology, where only specific fixed concentrations of antibiotics are studied. Using this methodology, numerous studies have observed synergistic interactions between polymyxins and various other antibiotic classes, including carbapenems, tigecycline, rifampin, and most recently, vancomycin (15)(16)(17)(18)(19)(20)(21)(22). These time-kill and checkerboard experiments, however, ignore the contribution of human pharmacokinetics and the dynamic effects of varied drug concentrations over the duration of the experiment.…”
mentioning
confidence: 99%